Control Co-design and Characterization of a Power Takeoff for Wave Energy Conversion based on Active Mechanical Motion Rectification. Issue 20 (2021) - Yang, Lisheng; Huang, Jianuo; Congpuong, Nob; Chen, Shuo; Mi, Jia; Bacelli, Giorgio; Zuo, Lei
Abstract: This paper presents a new power takeoff (PTO) design for wave energy converters (WEC). This design, inspired by active synchronous electrical rectifiers, not only can rectify the oscillating wave motion into a unidirectional motion, but also guarantee the generator can control the WEC structure throughout the operation as a motor. The active mechanical motion rectification (AMMR) mechanism used in this design is presented, as well as an example PTO assembly for an oscillating surge WEC. The whole system dynamics is then modelled and simulated to show the functions of the PTO with AMMR. Experimental demonstration and characterization are conducted with a partial prototype.